Conflicting interactions in the middle of the seventeenth century: Rome and the monarchies of Spain and France in a Jesuit speech - García, Facundo (Cuadernos de Historia Moderna, 2018)
In the middle of the seventeenth century, the Monarchy of Spain underwent a series of processes that partly explained some of the changes that occurred during the second half of the century. Among them, the discussion of the identity of the monarchy, the struggle for European hegemony, its complex relationship with the Holy See, and the role of the Order of Jesus in this context are the most important ones. In this paper we will analyze the convergence of the described processes through the study of a manuscript written in Rome in 1662 by Jesuit Father Nicolás Martínez: “Exclusiva de Reyes: si se debe atender a la elección del Sumo Pontífice de Roma”. We believe that in the core of this exclusive appeal by the Crown circumstances like the interpretation some men of the time made of the context, the design of the Catholic Monarchy at the international level, the development of new power strategies after the fall of the Olivares regime by the Jesuits, could be understood.
Keywords: XVIIth century; Monarchy of Spain; Monarchy of France; Rome; Nicolás Martínez; Exclusiva; identities; politic.